PENGARUH INTENSITAS MODAL, PERTUMBUHAN PENJUALAN, DAN CSR TERHADAP PENGHINDARAN PAJAK PADA SEKTOR PERUSAHAAN KONSTRUKSI YANG TERDAFTAR DI BEI PERIODE 2019-2023 - Arya Daiva; Rohma Septiawati; Fista Apriani Sujaya (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2025)
Businesses in Indonesia usually utilize tax avoidance as a strategy to reduce their tax liabilities without breaking the law. This study aims to investigate the relationship between tax avoidance and capital intensity, sales growth, and Corporate Social Responsibility (CSR) in construction companies listed between 2019 and 2023 on the Indonesia Stock Exchange (IDX). This study utilizes quantitative techniques and secondary data. A purposeful sampling strategy was used to select 16 sample companies for this investigation. SmartPLS 4.0 was used to process the data. According to the research findings, tax avoidance is not significantly affected by capital intensity or sales growth. Tax avoidance is significantly affected by Corporate Social Responsibility (CSR), which suggests that businesses with greater CSR tend to have fewer tax avoidance strategies. These results have consequences for regulators creating more efficient tax laws for Indonesia's building industry.